Numerical Analysis of the Influence of Frost Layers on the Heat Transfer Characteristics of Cryogenic Valves for Polar LNG Ships - Shengpeng Li; Baolong Lin; Xu Bai; Pengyu Wei; Lian Wang; Ruonan Zhang (Energies)
To investigate the impact of frost-layer formation on the heat transfer characteristics of cryogenic valves in LNG vessels, this study derived the temporal variation in the valve’s temperature field based on the thermodynamic characteristic parameters of the low-temperature valve. Additionally, a frost formation model was developed for the drip tray. This considered the physical model characteristics of the tray, and the frost thickness was calculated for different times. The morphology of the calculated frost layer was coupled with the low-temperature valve model for heat transfer calculations to explore the influence of the frost layer on valve heat transfer characteristics. The results show that, in the initial stage of frost formation, the frost layer acts similarly to a finned heat sink, enhancing the thermal exchange efficiency at the surface of the drip tray, which results in a temperature increase in the drip tray and stuffing box compared to the frost-free condition. However, as the frost layer grows on the surface of the drip tray, the surface heat transfer resistance increases, gradually diminishing the enhancing effect of the frost layer on the heat dissipation of the drip tray. The results validate the dual role of the frost layer in the heat transfer process of low-temperature valves, providing important insights for the design and optimization of such valves.